THE CREATION OF ANALYTICAL PREDICATION CONCEPT IN MULTILEVEL ORGANIZATION SYSTEM MANAGEMENT - O. M. Pisareva (Модернизация, инновация, развитие)
This article deals with analytical and forecasting methodology problems in the integrated business systems management. The theoretical framework of analytical predication concept in multilevel organization systems is presented.